Effects of 16-Week Consumption of Caffeinated and Decaffeinated Instant Coffee on Glucose Metabolism in a Randomized Controlled Trial - Ohnaka, Keizo (Hindawi Publishing Corporation, 2012)
Objective. Observational studies have shown a protective association between coffee consumption and type 2 diabetes mellitus whereas caffeine or caffeinated coffee acutely deteriorates glucose tolerance. We investigated the effects of chronic drinking of instant coffee on glucose and insulin concentrations during a 75 g oral glucose tolerance test. Methods. Overweight men with a mild-to-moderate elevation of fasting plasma glucose were randomly allocated to a 16-week intervention of consuming 5 cups of caffeinated (n = 17) or decaffeinated (n = 15) instant coffee per day or no coffee (n = 13). Results. The caffeinated coffee group showed statistically significant decreases in the 2-hour concentrations and the area under the curve of glucose while neither decaffeinated coffee nor coffee group showed such a change. Waist circumstance decreased in the caffeinated coffee group, increased in the decaffeinated coffee group, and did not change in the noncoffee group (P = 0.002). With adjustment for the change in waist circumference, caffeinated and decaffeinated coffee consumption were associated with a modest decrease in the postload glucose levels. Conclusion. Both caffeinated and decaffeinated coffee may be protective against deterioration of glucose tolerance.